APPARATUS FOR LOCALIZATION AND DOSIMETRY OF WOUNDS WITH RADIOACTIVE CONTAMINATION. Issue 9 (22nd August 2022) - Slavíček, Tomáš; Broulím, Jan; Fojtík, Pavel; Prokop, Matěj; Rubovič, Peter
Abstract: Disasters involving radioactive materials are one of the most dangerous accidents a living organism can be exposed to. Individuals and first responders are in risk during accidents or interventions, due to radioactive debris impact, due to the use of depleted uranium ammunition or a malevolent act against individuals. Moreover, radioactive contamination of wounds causes internal exposure in the body and standard decontamination procedures cannot be applied. In order to deal with such situations, we are developing a measurement system consisting of a robotic arm, an array of various detectors and a corresponding methodology, which allows quantifying timely the spatial distribution of contamination and the radiation dose for the adequate medical response. The aim of this publication is to the present current status of the development of the described apparatus.